Green Roof Performance in Cold Climates : A study on how different plants suited for the subarctic climate in northernSweden affects the performances of green roofs - Hjelm, Jonathan (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2019)
Increased urbanization leads to an increasing amount of impervious surfaces and a decrease ofthe natural hydrological function. Urban stormwater does thus risk to create high surface flows which could damage the receiving water bodies (e.g. erosion) or the urban area itself (flooding). Integrating more nature-based systems into the urban area increases the natural hydrological function and the risks for high surface flows are lowered. One way of implementing nature-based systems in the urban environment is to install green roofs. Most of the research and development done on green roofs have been focusing on the conditions of central Europe. Installing green roofs with the same vegetation in the subarctic climate of northern Sweden would expose it to a climate it might not be suited for, and growth would be limited. The vegetation helps increase the retaining and detaining capabilities of the green roofs and therefore the purpose of this thesis was to examine if planting native vegetation would help increase thegreen roofs performance in a subarctic climate. Conventional green roofs vegetated with sedum was hypothesized to have lessened retaining and detaining capabilities when placed in cold climates since the vegetation was exposed to a climate it probably was not suited for. It was examined whether planting more native vegetation could help increase green roofs performance. The vegetation was chosen based on Grime´s “universal adaptive strategy theory”, which describes competitors, stress tolerators and ruderals as three different vegetation groups with different survival strategies. Different species from each strategy were selected and planted on the roofs. There were five roofs per survival strategy and five roofs where all strategies were mixed. Conventional sedum vegetation was planted on five roofs to be able to compare green roofs performance. Five control roofs with substrate only and one reference roof made of steel were installed as well. In total, seven rainfall events were analyzed, and few ...